2000
DOI: 10.1309/xwfe-armn-hg2d-ajyv
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Telomerase hTERT Protein and hTR in Benign Mucosa, Dysplasia, and Squamous Cell Carcinoma of the Cervix

Abstract: Telomerase has been detected by telomerase repeat amplification protocol (TRAP) assay in cervical dysplasia and squamous cell carcinoma but not in most normal cervical tissues. In the present study, the cellular localization of the protein catalytic subunit of telomerase (hTERT) and the RNA component (hTR) were investigated by a sensitive immunohistochemical technique and by in situ hybridization, respectively. hTERT protein was detected in all diagnostic categories of cervical specimens. hTERT was localized p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
56
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 19 publications
10
56
0
Order By: Relevance
“…Less sensitive methods have failed to reveal speci®c localization of telomerase in our hands, although other groups have reported success in some tissues using conventional avidin ± biotin-based immunoperoxidase methods . Studies in our laboratory showed that hTERT protein is predominantly localized to lower portions of the suprabasal squamous cells of normal or benign-reactive cervical mucosa (Frost et al, 2000). By contrast, almost fullthickness distribution of nuclear staining was observed in nearly all cases of moderate and severe dysplasia (Frost et al, 2000).…”
Section: Histologic Localization Of Telomerasementioning
confidence: 87%
See 3 more Smart Citations
“…Less sensitive methods have failed to reveal speci®c localization of telomerase in our hands, although other groups have reported success in some tissues using conventional avidin ± biotin-based immunoperoxidase methods . Studies in our laboratory showed that hTERT protein is predominantly localized to lower portions of the suprabasal squamous cells of normal or benign-reactive cervical mucosa (Frost et al, 2000). By contrast, almost fullthickness distribution of nuclear staining was observed in nearly all cases of moderate and severe dysplasia (Frost et al, 2000).…”
Section: Histologic Localization Of Telomerasementioning
confidence: 87%
“…In situ hybridization has demonstrated that hTR is largely restricted to the basal and parabasal cell layers of ectocervical mucosa, metaplastic squamous epithelium, or LSIL, although focal expression has also been observed in some histologically normal endocervical glands (Yashima et al, 1998;Frost et al, 2000). By contrast, hTR was detected throughout all layers of the lesional mucosa in moderate dysplasia, severe dysplasia, and in carcinoma in situ (Yashima et al, 1998;Frost et al, 2000;Wisman et al, 2000). Nakano et al (1998) demonstrated that hTR and hTERT mRNA are colocalized in cervical SCCs as well as in benign and dysplastic cervical mucosa biopsy specimens.…”
Section: Histologic Localization Of Telomerasementioning
confidence: 99%
See 2 more Smart Citations
“…17,24,25 Telomerase is a ribonucleoprotein DNA polymerase containing an RNA component, designated hTR, and a single catalytic protein subunit, human telomerase reverse transcriptase (hTERT), which directs the synthesis of telomeric DNA repeats. Telomerase contributes to cellular immortalization as a fundamental component of the processes of malignant transformation and may play a central role in HPV-mediated transformation of the cervical mucosa.…”
mentioning
confidence: 99%